If Everyone Is Doing It, It Must Be Safe: College Students' Development of Attitudes toward Poly-Substance Use. (19th September 2019) - Willis, Erin; Adams, Robyn; Keene, Justin
Abstract: Background : While binge drinking on college campuses has been a topic of concern for decades, especially among fraternity and sorority members, recreational drug use is on the rise and mixing alcohol and drugs is now more of a concern than ever. Objective : Social learning theory was used as a framework for understanding how students develop attitudes regarding the possible risks and rewards of various behaviors such as binge drinking and drug use. Method : This research reports the results of 13 focus group discussions with 63 college students. A thematic approach was used and revealed several themes: participating in college culture, experimenting is expected, ignoring risk-taking, and resisting peer pressure. Findings : Participants felt as if it was expected that college students would experiment with alcohol and drugs, and that it was just "part of going away to college." Students reported ignoring the known risks of mixing alcohol and drugs use despite prior education efforts. Conclusions : The findings of this study suggest that alcohol and drug use on college campuses is, at least in part, driven by a perception of college culture and a poor balancing of the risks and rewards associated with these behaviors.